2005
DOI: 10.1038/sj.bjc.6602829
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication licensing and cell cycle kinetics of normal and neoplastic breast

Abstract: Mcm2 -7 (MCM) proteins are part of the origin licensing machinery that regulates initiation of DNA replication. Geminin is a licensing repressor and prevents reinitiation of DNA replication during S -G2 -M phase by blocking reloading of Mcm2 -7 at replication origins. Here, we have analysed these replication licensing factors (RLFs) to determine whether the pathway becomes deregulated during mammary carcinogenesis, and have assessed their potential value as prognostic markers. Protein expression profiles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 38 publications
10
77
1
1
Order By: Relevance
“…The largest growth fraction is identified by Mcm2, reflecting identification of both cycling and non-cycling cells with proliferative potential. The lower growth fraction identified by geminin compared with Ki67 is in keeping with its expression being restricted to S-G2-M phase Wharton et al, 2004;Dudderidge et al, 2005;Shetty et al, 2005). In vitro, increased MEK5/ERK5 signalling leads to increased Mcm2, geminin, and Ki67 protein levels.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The largest growth fraction is identified by Mcm2, reflecting identification of both cycling and non-cycling cells with proliferative potential. The lower growth fraction identified by geminin compared with Ki67 is in keeping with its expression being restricted to S-G2-M phase Wharton et al, 2004;Dudderidge et al, 2005;Shetty et al, 2005). In vitro, increased MEK5/ERK5 signalling leads to increased Mcm2, geminin, and Ki67 protein levels.…”
Section: Discussionmentioning
confidence: 70%
“…RLFs, which form the core of the initiation machinery, act as relay stations coupling growth regulatory and DNA damage response pathways to chromosomal replication. We and others have demonstrated that dysregulation of the replication Ki67 Geminin P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r P C 3 -E R K 5 P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r initiation machinery is an early event in tumourigenesis and that the Mcm2-7 RLFs are powerful diagnostic and prognostic markers in a wide range of tumour types (Williams et al, 1998Stoeber et al, 1999;Wharton et al, 2001Wharton et al, , 2004Davies et al, 2002;Going et al, 2002;Stoeber et al, 2002;Gonzalez et al, 2003;Kruger et al, 2003;Padmanabhan et al, 2004;Dudderidge et al, 2005;Korkolopoulou et al, 2005;Shetty et al, 2005). Recent reports have shown that the MEK5/ERK5 pathway is implicated in the regulation of cell proliferation, and that increased MEK5/ERK5 signalling results in increased cell proliferation, invasion and metastatic spread during prostate carcinogenesis Mehta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations